إتجاهات الشباب الجامعي في مشاهدة الفضائيات وتأثيراتها المحتملة على القيم والسلوك : دراسة ميدانية - البياتي، ياس خضير (الجمعية المصرية للعلاقات العامة, 2014)
تهدف هذه الدراسة إلي التعرف على التأثيرات الاجتماعية المحتملة للصورة المتلفزة على الشباب الخليجي ومدى تأثيرها على حياته والميكانيزمات العلمية لتحقيق أمنه الاجتماعى وتوازنه السيكولوجى إزاء المضامين السلبية التي تبثها هذه الفضائيات، والحد من تفاقم ظاهرة عادات المشاهدة الخاطئة والتقليل من مضارها الاجتماعية، وهي دراسة ميدانية أجريت على طلبة جامعة عجمان في دولة الإمارات العربية المتحدة. لذلك فإن البحث سعى إلى تحقيق بعض الأهداف الرئيسية، وأبرزها إيضاح طبيعة سلطة الصورة المتلفزة وتأثيراتها الاجتماعية على الشباب والتعرف على المضامين السلبية التي يتم تسويقها للشباب من خلال الصورة المتلفزة. وقد اعتمدنا في هذه الدراسة المنهج الاستطلاعي باعتباره المنهج الملائم لتحقيق أهداف الدراسة. وتم استخدام الاستمارة الاستبيانية التي وزعت على (٢٠٠) طالبة وطالبة تم اختيارهم من ست كليات من جامعة عجمان باستخدام العينة العشوائية الطبقية المنظمة. وأظهرت نتائج البحث بوجود ضعف في الثقافة المتلفزة التي يتغذى بها الشباب والتي لا تمنحها أدنى المقومات الأساسية لتأهيله، حيث ساهمت هذه الثقافة إلى حد بعيد في خلق الاضطراب الاجتماعي، وعدم الاستقرار الاجتماعي، وتعميق المشاعر الذاتية أكثر من الالتزام الجماعي، وتنمية الفردية والروح الاستهلاكية، وضعف دور الأسرة والمدرسة في عملية التنشئة الاجتماعية مقابل الدور الكبير المؤثر لوسائل الإعلام والمعلومات على اتجاهات التنشئة الاجتماعية والعمليات الاجتماعية. This study aims to identify the possible social effects of televised pictures or visual images on the lives of the Arab youth in order to clarify the nature of the authority of the televised images and their social effects on the youth. Therefore, it focuses on the scientific mechanisms for achieving the social security and psychological balance of the youths in relation to the negative contents broadcast by satellite channels.. The study also seeks to investigate ways of limiting the phenomenon of bad viewing habits to minimize its harmful social effects. It is basically a field study, conducted on a sample of students from Ajman University of Science & Technology (AUST) in the United Arab Emirates (UAE). The questionnaire method has been used, as it is considered to be appropriate to the aims of the study. A questionnaire form has been designed and distributed to( 9200) male and female students affiliated to six colleges of AUST colleges, using the random class sample. The results of the research show a weakness in the youth's television culture, a culture which lacks the basic elements needed to qualify the youth for this experience. This culture has largely contributed to the social confusion and social instability of the youth. In addition, the weak viewing culture has reinforced the youth's personal feelings at the expense of social commitment, has helped to develop individualism and consumerism, has weakened the role of the family and school in the process of social upbringing in contrast with the big and influential role of the mass and information media in shaping the trends of social upbringing and social processes.
Keywords: وسائل الإعلام -- القنوات الفضائية -- الشباب الجامعي -- القضايا الإجتماعية